Sustainable Landscape Construction: Materials and Products — Concrete - Gail Hansen (EDIS)
ENH1146, a 1-page fact sheet by Gail Hansen, describes environmental issues, design strategies, and construction techniques for using concrete in landscape construction. Includes references. Published by the UF Department of Environmental Horticulture, October 2009.